PS01.176: OPEN VERSUS HYBRID VERSUS MINIMALLY INVASIVE ESOPHAGECTOMY FOR PATIENTS WITH ESOPHAGEAL CANCER: A PROPENSITY SCORE MATCHED ANALYSIS. (14th September 2018) - Visser, Els; Edholm, David; Smithers, Mark; Thomas, Janine; Brosda, Sandra; Krause, Lutz; Thomson, Iain; Gotley, David; Barbour, Andrew
Abstract: Background: MIE is becoming more common and is considered safe. There are few studies supporting laparoscopy in favor of laparotomy for the abdominal part of a three-field esophagectomy and long term survival data are scarce. The objective was to compare open esophagectomy (OE), with hybdrid thoracoscopic-laparotomic esophagectomy (HMIE) and minimally invasive esophagectomy (MIE) with regard to surgical outcomes, postoperative complications and survival. Methods: A prospective database of esophageal resection for cancer at a single centre identified 243 OE, 688 HMIE and 80 MIE procedures. Propensity scores were used to match 80 patients in each group adjusting for age, gender, weight, clinical stage, neoadjuvant treatment, and year of surgery. Results: Respiratory complications were more common after OE (49%) than after MIE (31%, P  = 0.02). Median operative time was longer for MIE (330 minutes) versus HMIE or OE (both 300 minutes, P  < 0.001). Median length of stay was shorter following MIE (12 days) compared with HMIE (14 days) and OE (15 days), P = 0.001. There were no significant differences between groups with respect to other complications, median number of lymph nodes examined (22–23 for all groups), or R0 resection rate (range 85–91%) for all groups. There was no difference in 5-year overall survival between groups. Conclusion: Compared with OE and HMIE, MIE was associated with shorter length of stay and fewer respiratory complications, but longer operative time. Thus, there may be additional benefit for MIE without comprising oncological outcomes. Disclosure: All authors have declared no conflicts of interest.